A stellar overdensity associated with the Small Magellanic Cloud. Issue 2 (28th February 2017) - Pieres, A.; Santiago, B. X.; Drlica-Wagner, A.; Bechtol, K.; Marel, R. P. van der; Besla, G.; Martin, N. F.; Belokurov, V.; Gallart, C.; Martinez-Delgado, D.; Marshall, J.; Nöel, N. E. D.; et al.
Abstract: We report the discovery of a stellar overdensity 8° north of the centre of the Small Magellanic Cloud (SMC; Small Magellanic Cloud Northern Over-Density; SMCNOD), using data from the first 2 yr of the Dark Energy Survey (DES) and the first year of the MAGellanic SatelLITEs Survey (MagLiteS). The SMCNOD is indistinguishable in age, metallicity and distance from the nearby SMC stars, being primarily composed of intermediate-age stars (6 Gyr, Z =0.001), with a small fraction of young stars (1 Gyr, Z =0.01). The SMCNOD has an elongated shape with an ellipticity of 0.6 and a size of ∼ 6° × 2°. It has an absolute magnitude of M V  ≅ −7.7, r h  = 2.1 kpc, and μ V ( r  <  r h ) = 31.2 mag arcsec −2 . We estimate a stellar mass of ∼10 5 M⊙, following a Kroupa mass function. The SMCNOD was probably removed from the SMC disc by tidal stripping, since it is located near the head of the Magellanic Stream, and the literature indicates likely recent Large Magellanic Cloud-SMC encounters. This scenario is supported by the lack of significant H i gas. Other potential scenarios for the SMCNOD origin are a transient overdensity within the SMC tidal radius or a primordial SMC satellite in advanced stage of disruption.